Use of sample size calculation in scientific research in Brazilian Physical Education journals - Crozara, Luciano Fernandes; Sponton, Amanda Christine Da Silva; Jarrete, Aline Pincerato; Araujo, Hygor Nunes; Huamaní, Oscar Gutiérrez; Fernandes, Rômulo Araújo (Universidade Federal de Santa Catarina, 2014)
The mistaken use of biostatistics in scientific research involves methodological errors both in the research itself as in its analyses. Among these, the lack of sample size calculation, considered essential for validation and credibility of results, is often found. The aim of the study was to determine how often sample size calculation is used in articles published in Physical Education national journals. The study included only national scientific journals ranked as A1 and B2 by the Coordination of Improvement of Higher Education Personnel (CAPES), which analyzed only articles available in full and published in the period from 2010 to 2012. Review articles, letter to the editor, points of view and original articles that did not perform any statistical analysis were excluded. Approximately 15 % of articles analyzed performed sample size calculation and no difference between these proportions over the years were identified. Differences between Physical Education subareas (education, health and sport) were observed, being lower in sport (p = 0.001) compared to other subareas. Journals classified as B2 showed higher use of sample size calculation in relation to those classified as B1 (p = 0.013) and A2 (p = 0.007). The use of sample size calculation in scientific research published in Physical Education national journals in the period from 2010 to 2012 was not satisfactory, especially in sport subarea. Moreover, no evolution on the use of sample size calculation over the years analyzed was observed.

O emprego equivocado da bioestatística nas pesquisas científicas implica em erros metodológicos tanto na condução quanto nas análises das mesmas. Dentre estes, a ausência do cálculo amostral, considerado primordial para validação e credibilidade dos resultados, é frequentemente encontrado. O objetivo do estudo foi verificar com que frequência o cálculo amostral é empregado nos artigos publicados em periódicos nacionais de Educação Física. Foram incluídos no estudo somente periódicos científicos nacionais classificados entre A1 e B2 pela Coordenação de Aperfeiçoamento de Pessoal de Nível Superior (CAPES), dos quais foram analisados somente artigos originais disponíveis na íntegra e publicados no período de 2010 a 2012. Foram excluídos do estudo artigos de revisão, carta ao editor, ponto de vista e artigos originais que não realizaram nenhum tipo de análise estatística. Aproximadamente 15% dos artigos analisados realizaram cálculo amostral; não houve diferença entre as proporções destes ao longo dos anos. Observou-se diferença entre as subáreas da Educação Física (educação, saúde e esporte), sendo menor na subárea esporte (p=0,001) em relação às demais. Os periódicos classificados como B2 apresentaram maior uso do cálculo amostral em relação àqueles classificados como B1 (p=0,013) e A2 (p=0,007). O emprego do cálculo amostral em pesquisas científicas publicadas em periódicos nacionais de Educação Física no período de 2010 a 2012 não foi satisfatório, especialmente na subárea esporte. Além disso, não foi observada uma evolução do uso do cálculo amostral ao longo dos anos analisados.
Emprego do cálculo amostral em pesquisas científicas de periódicos nacionais de Educação Física
Keywords: Educação física; Estatística; Tamanho da amostra; Physical education; Sample size; Statistics